Cipta Karya Seni Tari Anak Sekolah Dasar Berpijak Pada Permainan Tradisional - Sari, Ayu Titis Rukmana; Wahyudi (JURNAL PENDIDIKAN DASAR NUSANTARA, 2021)
Abstract: This study is a study of children’s dance artwork development based on traditional games which in the creation process is done through several stages, namely: Observation Stage, Exploration Improvement and Composition in order to reach the maximum quality. The novelty value of this dance creation is an idea about traditional games which is carried out at a performance of new dance creation for children in Elementary Schools, expecting that this can attract children’s interest to be more fond of traditional games which is one of locality wealth and have character learning. The traditional games become the source of this creation is Hide and Seek/Obak Dhelik (in Javanese). Originality assessment, novelty, and applicability of the creation are assessed by two dance experts which can be responsible in giving the assessment. Dhelikan dance work is able to be appreciated on youtube link: https://www.youtube.com/watch?v=Y2M-KacYfpw.